ANALISIS HUKUM PEMBUATAN AKTA WASIAT DI HADAPAN NOTARIS YANG DIBATALKAN OLEH PENGADILAN (Studi Putusan Mahkamah Agung Nomor 3124K/PDT/2013) - Putra Alexander Sitepu (Nommensen Journal of Legal Opinion, 2022)
The objectives of this research are to discover and analyze the implementation of inheritance law according to the laws prevailing in Indonesia, to discover contradiction of legal protection for holder of the right of building whose property is inherited to another person, in relation with the verdict of the Supreme Court No. 3124 K/Pdt/2013, and to discover as well as to analyze the legal consequences for the deed of will containing an object that should not have been inherited inrelation with the District Court Ruling No. 53/Pdt.G/2012/Pn. Jkt Selatan. The deed of will drawn up by a notary resulted from his negligence has the power to be evidence that proves it as an underhanded deed, which contains mistakes as violation performed by the notary or defects in its form. In addition, it may be annulled when the deed of will harms another party and the harmed party requests for civil annulment to the Judge with evidence. According to the provisions inArticle 84 of the Notarial Act, such deed has the power to prove it as an underhanded deed, so it may be annulled when the harmed party is able to prove it in the court. The drawing up of a deed must fulfill three element, namely physical, formal and material elements. If one of the elements is not true, it may cause a civil case which truth can be proven. As to the implementation of the inheritance law in the verdict, it is stated that the illegal action in drawing up the deed of will; inwhich the defendant puts property of the plaintiff in his will grounded on a deed of will, is annulled to guarantee legal protection for the plaintiff (article 1365 of the Civil Code). Furthermore, the drawing up of the will is declared to be null and void because the person appearing is not in good health state or is not healthy. As to its legal consequences, that the property contained in the will does not belong to the inheritor. the deed becomes null and void according to article 834 of the Civil Code. As previously mentioned. The annulment of the deed guarantees the rights of the plaintiff whose property was previously put in the defendant's will.